Construction of orthogonal CC-sets - Brodnik, Andrej; Jovičić, Vladan; Palangetić, Marko; Silađi, Daniel (Informatica, 2019)
In this paper we present a graph-theoretical method for computing the maximum orthogonal subset of a set of coiled-coil peptides. In chemistry, an orthogonal set of peptides is defined as a set of pairs of peptides, where the paired peptides interact only mutually and not with any other peptide from any other pair. The main method used is a reduction to the maximum independent set problem. Then we use a relatively well-known maximum independent set solving algorithm which turned out to be the best suited for our problem. We obtained an orthogonal set consisting of 29 peptides (homodimeric and heterodimeric) from initial 5-heptade set. If we allow only heterodimeric interactions we obtain an orthogonal set of 26 peptides.